Pembelajaran Pendidikan Agama Islam Humanistik dengan Pendekatan Active Learning di SDN Nugopuro Gowok - Nasution, Hambali Alman; Suyadi, Suyadi (Jurnal Pendidikan Agama Islam, 2020)
This study aims to find out how the application of the theory of humanistic learning in Islamic Religious Education learning, would like to know the results of Islamic religious education learning through the theory of humanistic flow with the method (active learning) in SDN Nugopuro Gowok. The type of research used in this study is descriptive qualitative method using data collection such as interviews, observation and documentation. Based on the results of the study that the application of the theory of humanistic learning (active learning) in PAI learning in SDN Nugopuro Gowok has been done quite well and has been going well by educating and guiding students to learn to use various methods or strategies actively. It was marked by positive responses and changes in behavior such as, interactive, learning motivation, strengthening memory and tolerance.